STUDENT PERCEPTIONS ON DEVELOPING AN ANTI-CORRUPTION CULTURE IN HIGHER EDUCATION - Kulsum Nur Hayati; Shaleh; Syahrul Ramadhan (International Journal of Cultural and Social Science, 2025)
This study aims to understand students' perceptions on developing an anti-corruption in higher education (BKAK) in Indonesia. The researchers used a combined method involving surveys (quantitative) and interviews (qualitative). A total of 95 students from undergraduate (S1) and graduate (S2) programs were randomly selected through google forms to measure various aspects of their perceptions of BKAK. Survey data were processed using descriptive statistics. Qualitative interviews focused on important values in strengthening BKAK according to students' views, then analyzed using techniques from Miles, Huberman, & Saldana (2014) with the help of NVivo 14 Plus. The results of the study indicate a high awareness among students of the importance of an anti-corruption culture in higher education institutions, as well as their readiness to engage in related initiatives. Interview analysis revealed that integrity, honesty, transparency, and collective responsibility are considered key values in strengthening BKAK. Students also emphasized the importance of anti-corruption education in the curriculum and the role of role models from higher education leaders. The results of this study demonstrate the need for a holistic approach that involves integrating BKAK values into policies and curricula, as well as empowering students as agents of change. This research provides important insights for policymakers and educators in designing effective strategies to increase student participation and engagement in promoting and maintaining an anti-corruption culture in higher education.